2017
DOI: 10.24095/hpcdp.37.2.04
|View full text |Cite
|
Sign up to set email alerts
|

The burden of generalized anxiety disorder in Canada

Abstract: Introduction: Although generalized anxiety disorder (GAD) is common and disabling, there are few Canadian studies on this mental illness. We compared the characteristics, health status, health services use and health care needs of Canadians with GAD to those with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 29 publications
4
44
0
1
Order By: Relevance
“…46 Just over half of those in our study were married or in a common-law relationship, which is slightly higher than those found in other Canadians studies. 38,39 It is worth noting that these other studies further demonstrate that those with mood and anxiety disorders were less likely to be married or in a commonlaw relationship than those unaffected by these disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…46 Just over half of those in our study were married or in a common-law relationship, which is slightly higher than those found in other Canadians studies. 38,39 It is worth noting that these other studies further demonstrate that those with mood and anxiety disorders were less likely to be married or in a commonlaw relationship than those unaffected by these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…47 The proportion of those with post-secondary education in our study was similar to the findings from other Canadian studies. 38,39,48 All aforementioned studies found people with mood and anxiety disorders completed post-secondary education in the same proportion as those without these disorders. 38,39 However, when broken down by type of post-secondary education attained, people with these disorders were less likely to have a post-secondary education at the Bachelor level or above than those who were not affected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelletier and coauthors 2 estimate that 700 000 Canadians report symptoms consistent with generalized anxiety disorder (GAD) and that 30% of these individuals' needs for health care are not being met. Amankwah The focus on the relationship between diabetes and excess weight by Bilandzic and Rosella is appropriate as we estimate that 62% of type 2 diabetes in Canada is attributable to excess weight.…”
mentioning
confidence: 99%